Pedagogical projection of teaching digital competition. The case of a cooperative education - López Belmonte, Jesús; Pozo Sánchez, Santiago; Ávila Rodríguez, Martha; Montero Cáceres, Celia (IJERI: International Journal of Educational Research and Innovation, 2020)
The society in which we require the teaching staff to acquire professional skills concerning the technological field, in order to meet the needs of a student involved in a digital era. The aim of this study has focused onmeet the educational scope of the digital competence of teachers of a cooperative education. For this it has followed a non-experimental design research with quantitative descriptive nature, in a sample of 42 teachers teaching a cooperative Ceuta (Spain). As data collection instrument has been used an ad hoc questionnaire. It has been obtained that participants with higher educational projection in the field of ICT are in a male profile, young age, with a degree as academic qualifications played teaching at the stage of compulsory secondary education. However, the level of digital competence revealed by these professionals in education is deficient, reflecting only digital skills in the related information and digital literacy area.